Full-frequency correction of spatial impulse response in back-projection scheme using space-variant filtering for optoacoustic mesoscopy - Tong Lu; Yihan Wang; Jiao Li; Jaya Prakash; Feng Gao; Vasilis Ntziachristos (Photoacoustics, 2020)
The fidelity and quality of reconstructed images in optoacoustic mesoscopy (OPAM) can be significantly improved by considering the spatial impulse response (SIR) of the employed focused transducer into reconstruction. However, the traditional method fully taking the SIR into account can hardly meet the data-intensive requirements of high resolution OPAM because of excessive memory and time consumption. Herein, a modified back-projection method using a space-variant filter for full-frequency correction of the SIR is presented, and applied to the OPAM system with a sphere-focused transducer. The proposed method can readily manage the large datasets of the OPAM and effectively reduce the extra time consumption. The performance of the proposed method is showcased by simulations and experiments of phantoms and biological tissue. The results demonstrate that the modified back-projection method exhibits better image fidelity, resolution and contrast compared to the common and weighted back-projection methods that are not or not fully accounting for the SIR.